상악 구치부 임플랜트 보철수복시 치관/치근비에 따른 응력 분포에 대한 유한 요소 분석 - 김진호; 김형섭; 최대균; 권긍록; Kim, Jin-Ho; Kim, Hyung-Seob; Choi, Dae-Gyun; Kwon, Kung-Rock (Taehan Chikwa Poch'ol Hakhoe chi, 2006)
Statement of the problem: In cases of low bone level in maxilla followed by extraction due to severe periodontitis or enlarged maxillary sinus, crown-root ratio of implant prosthesis will increase. The prognosis of these cases is not good as expected. Purpose : The purpose is to compare stress distribution due to crown-root ratio and effect of splinting between two implants in maxillary molar area under different loads Material and methods: Using ITI($4.1{×}10$ mm) implant. two finite element models were made(model S: two parallel implants, model A: one of two is 20 degree inclined). Each model was designed in different crown-root ratio(0.7:1, 1:1, 1.25:1) and set cement type gold crown to make it splinted or non-splinted clinical situations. After that, 300 N force was loaded to each model in four ways.(load 1 : middle of occlusal table, load 2 : middle of buccal cusp, load 3 : middle of lingual cusp, load 4 : horizontal load to middle of buccal cusp), and stress distribution was analyzed. Results: On all occasions, stress was concentrated on neck of implant near cortical bone. In the case of inclined implant, stress was increased compared with parallel implants. Under load 1, 2, 3, stress was not increased even when crown-root ratio increases, but under load 4, when crown-root ratio increases, stress also increased. And more stress was concentrated under load 1 than load 2, 3. When crown-root ratio was same, stress under load 1, 2, 3 decreased when splinting, but under load 4, stress did not really decrease. Conclusion: Under vertical load, stress distribution related to crown-root ratio did not change. But under horizontal load, stress increased as crown-root ratio increases. Under vertical load, splinting decreased stress but under horizontal load, effect of splinting was decreased as condition of implant changes for the worse such as increase of crown-root ratio, inclined implant.